Respuesta de un hibrido promisorio de maíz forrajero a las densidades de siembra y fertilización en la zona de Quevedo - Amaiquema Rodríguez, Leonardo Steven (2019)
The maize (Zea mays L.), is a very important crop in the world that is easy to develop and its sowing continues because of its high biomass yields that can be used to feed cattle in milk and meat production. Therefore, the use of high population densities and fertilization in corn translates into better land use and increased production of forage biomass. This work was carried out at the Pichilingue Tropical Experimental Station located in the Mocache area during the rainy season of 2019. Its objective was to evaluate the response of a promising hybrid of forage corn to planting and fertilization densities in the Quevedo area. . A completely randomized block design with divided plots was used, the analysis of variance was performed and the averages were subjected to the Tukey test at 5% probability. In 18 treatments and four repetitions, three plant densities were evaluated: 100,000, 115,000 and 130,000 pl ha-1 and five types of fertilization plus an absolute control and the harvest was done at 70 DDS. Agronomic variables were evaluated: 50% flowering days of the useful area, leaf area, grain status at harvest, plant height at harvest, percentage of stem stems, stem diameter, leaf-stem ratio, index of prolificity, percentage of sterile plants, percentage of prolific plants, yield of fresh and dry matter, in addition an economic analysis of the treatments was carried out. Having as main result the production of fresh fodder the interaction of 130 000 pl ha-1, with NPKS fertilization, led to the highest yield, with 76,80 t ha-1. The most economical treatment happened with the interaction with the density 100 000 pl ha-1 and fertilization N, with the highest net profit of $ 5 780